2013
DOI: 10.1007/s00213-013-3276-5
|View full text |Cite|
|
Sign up to set email alerts
|

Neurosteroid interactions with synaptic and extrasynaptic GABAA receptors: regulation of subunit plasticity, phasic and tonic inhibition, and neuronal network excitability

Abstract: Rationale Neurosteroids are steroids synthesized within the brain with rapid effects on neuronal excitability. Allopregnanolone, allotetrahydrodeoxycorticosterone, and androstanediol are three widely explored prototype endogenous neurosteroids. They have very different targets and functions compared to conventional steroid hormones. Neuronal GABAa receptors are one of the prime molecular targets of neurosteroids. Objective This review provides a critical appraisal of recent advances in the pharmacology of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
191
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(195 citation statements)
references
References 332 publications
(495 reference statements)
2
191
0
2
Order By: Relevance
“…Under physiologic conditions, GABA A receptors, including synaptic receptors, are exposed to endogenous modulators such as neuroactive steroids (Carver and Reddy, 2013). Under clinical conditions, GABA A receptors can be exposed to GABAergic sedative drugs such as propofol, etomidate, or barbiturates.…”
Section: Introductionmentioning
confidence: 99%
“…Under physiologic conditions, GABA A receptors, including synaptic receptors, are exposed to endogenous modulators such as neuroactive steroids (Carver and Reddy, 2013). Under clinical conditions, GABA A receptors can be exposed to GABAergic sedative drugs such as propofol, etomidate, or barbiturates.…”
Section: Introductionmentioning
confidence: 99%
“…Synaptic GABAA receptors are activated transiently after the release of GABA from presynaptic vesicles, while extrasynaptic GABAA receptors are in general activated continuously, controlling neuronal excitability and the strength of synaptic transmission [37][38][39][40][41].…”
Section: Tonic and Phasic Inhibition By Gabaa Receptorsmentioning
confidence: 99%
“…In general, they potently enhance function of synaptic and extrasynaptic GABAA receptors by an allosteric mechanism [31,40,166,167]. Neurosteroids possess distinct, characteristic effects on the membrane potential and current conductance mainly via potentiation of GABAA receptors at low doses, and direct activation of receptor chloride channel at higher concentrations.…”
Section: Effects Of Neurosteroids At Gabaa Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This binding forces a conformation where GABA displays a higher affinity increasing the frequency of opening of the ion channel [234]. Similarly, several neurosteroids such as allopregnanolone will bind to the GABA-A ionophore and force conformational changes enhancing GABA effects [235,236]. Immunohistochemical studies have shown dense staining in spinal Rexed laminae for several alpha, beta and gamma subunits likely corresponding to primary afferents [237,238] presumably localized on primary afferent terminals.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%